Bisindolemethane derivatives as highly potent anticancer agents: Synthesis, medicinal activity evaluation, cell-based compound discovery, and computational target predictions. (January 2020) - Bahuguna, Ashish; Singh, Ashutosh; Kumar, Prateek; Dhasmana, Divya; Krishnan, Venkata; Garg, Neha
Abstract: In recent years chemical and biological interest in Turbomycin B and its various analogues have motivated researchers to develop new bioactive indole scaffolds. In this work, we focused on the development of indole alkaloids, especially bioindolemethane derivatives and their anticancer potential. Based on the excellent IC50 value against HeLa and A549 cell, cyano-substituted Turbomycin B (CN-TBM) was selected to understand the mechanism behind cancer cell death. The potential targets involved in CN-TBM mediated apoptotic cell death were predicted by comparing the results of two chemoinformatic approaches, i.e., PharmMapper and IdTarget. Four targets were predicted using these tools and the targets were further subjected to molecular docking to obtain a single target for CN-TBM. Serine/threonine-protein kinase (Pim-1) was identified as the direct target of CN-TBM with a pharmacophore model complementing well with the molecular features of CN-TBM. The interaction between CN-TBM and Pim-1 was well supported by high fit-score, Z-score, idTarget dock score and excellent binding affinity. Further, the present study also provides an insight into co-expression, shared protein domains, functional annotation and relationship within the ten putative targets of CN-TBM predicted by PharmMapper. Highlights: A series of bisindolemethane molecules were synthesized. The anti-cancer along with mode of cell death of synthesized molecules was evaluated. Drug-likeliness property was evaluated for all synthesized molecules. The potential cellular targets were predicted using chemoinformatic tools and verified using molecular docking approach. The drug target was further validated on glioma cell lines.